THE IMPLEMENTATION OF E-LKPD BY USING KNOW-WANT-LEARNED (KWL) STRATEGY ON GENETIC MATERIAL TOPIC TO TRAIN METACOGNITIVE SKILLS - Nisa', Alif Alia Khoirun; Susantini, Endang (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
The high school curriculum encourages students to have metacognitive skills. Genetic is one of the materials in biology that train metacognitive skills. Since the outbreak of Covid-19, the learning system has changed into online learning that causing new problems, such as teaching materials that are not able to facilitate students to train metacognitive skills. Teaching materials in the form of electronic student worksheet (E-LKPD) by using Know-Want-Learned (KWL) strategy assisted by the application of Ms. Office Word can be used to facilitate online learning. This research aims to describe the effect of implementing E-LKPD by using Know-Want-Learned (KWL) strategy on learning outcomes and student’s metacognitive skills. This study was conducted online using One Group Pre-test Post-test Design which was carried out at SMA Negeri 3 Tuban on 30 students on XII MIPA 1. The results showed that the implementation of learning obtained an average of 100% in the very practical category. The student’s responses obtained an average of 96.7% in the very practical category. Learning outcomes based on the pre-test and post-test score obtained the N-Gain Score’s average of 0.6%. The completeness of the item indicators with sensitivity score of ≥ 0.30. Metacognitive skills based on the average of increasing metacognitive score from poor category to the very good category. Thus it can be concluded that E-LKPD by using KWL strategyas a solution for the lack of material in the outbreak of Covid-19 is practical and effective to be applied in online learning to train metacognitive skills. Keywords: E-LKPD, metacognitive KWL, online learning.